Postoperative 30-day outcomes after craniotomy for supratentorial AVM resection in children. (December 2019) - Muir, Matthew; Patel, Rajan; Gadgil, Nisha; Pan, Iwen; Lam, Sandi
Highlights: The most common preoperative comorbidity was seizure disorder (32%). There was a low incidence (9%) of surgical and medical postoperative complications. Multiple perioperative variables were associated with poor outcome. Abstract: Purpose: To describe 30-day outcomes following craniotomy for arteriovenous malformation in children and identify risk factors for readmission, reoperation, and perioperative complication using the National Surgical Quality Improvement Program (NSQIP) Pediatric database. Methods: Patients aged 0–18 years who underwent surgery for arteriovenous malformations (years 2015–2016) were identified from the NSQIP Pediatric database. Descriptive statistics, uni-variate, and multi-variate regression analysis were performed using preoperative and perioperative data. The outcome of interest was postoperative adverse event including reoperation within 30 days, readmission within 30 days, discharge to rehab, and the complications wound infection/dehiscence, pneumonia, unplanned reintubation, pulmonary embolism (PE), renal insufficiency, urinary tract infection (UTI), stroke, venous thromboembolism (VT), and sepsis. Results: 167 patients were identified who met study criteria. 58% were male, and the majority had an ASA classification of 3 or greater (68%). 96 (57%) patients were found to have a preoperative comorbidity, with the most common comorbidity being seizure disorder (54 patients, 32%). 76 patients (46%) had documented perioperative events or complications. The incidence of wound infection/dehiscence was 4%; and of pneumonia, PE, unplanned reintubation, renal insufficiency, UTI, stroke, VT, sepsis were <1%. There were no deaths. The incidence of unplanned reoperation was 10% and unplanned readmission was 12%. Most (90%) were discharged to home. Operative time (p = .0001, OR = 9.53), emergent surgery status (p = .0001, OR = 8.19) and preoperative comorbidities (p = .007) were found to be significant predictors of poor outcome. Conclusion: In the NSQIP-P dataset, the incidence of perioperative complications and suboptimal outcomes among patients undergoing AVM resection were low.